Waterpipe Smoking Effect on Clinical Periodontal Parameters, Salivary Flow Rate and Salivary pH in Chronic ‎Periodontitis Patient - Al Mufti , Saif Mohammed T.; Saliem , Saif S. (Journal of Baghdad College of Dentistry, 2018)
Background: Waterpipe tobacco smoking has become common especially among young people, Waterpipe smoking misconcepted as a safer mean of smoking, so in this study we will highlight the effect of Waterpipe smoking ‎on periodontal and oral health.‎Materials and method. The selected ‎‎‎100 male subjects of 30-40 years, ‎categorized into 4 groups (each group ‎‎25 subject): Waterpipe smoker ‎with ‎healthy periodontium, ‎Waterpipe smoker ‎‎with chronic periodontitis, Non-‎‎smoker ‎with healthy periodontium and Non-smoker ‎with chronic periodontitis. Whole ‎unstimulated ‎saliva was collected. Clinical measurements: plaque ‎index, ‎gingival index, ‎bleeding on probing, salivary flow ‎rate ‎and ‎salivary pH were recorded‎.‎ ‎Results. In the healthy groups: plaque index and salivary pH were ‎higher in smokers than non-smokers but with no ‎significant difference (P>0.05). While gingival index and salivary flow rate were ‎higher in smoker than non-smokers and with significant ‎difference (p